2005
DOI: 10.1136/jcp.2004.017756
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercolarisinfection mimicking a malignant tumour in a non-immunocompromised patient. Diagnosis by bronchoalveolar cytology

Abstract: Autoinfective strongyloidiasis is often fatal in immunosuppressed patients or in immunocomprised hosts. An interesting case ofStrongyloides stercolarishyperinfection was seen in an immunocompetent patient. This report describes a case of fatal strogyloidiasis in a 79 year old man, who had suffered gastrointestinal discomfort for years, and who presented because of respiratory illness. A chest radiograph showed an irregular mass close to the mediastinum and interstitial infiltrates, but blood eosinophilia was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 15 publications
0
19
1
4
Order By: Relevance
“…An apparently immunocompetent patient developed hyper infection and died two days after having started therapy with thiabendazole [149]. Unfortunately autopsy was denied.…”
Section: Resultsmentioning
confidence: 99%
“…An apparently immunocompetent patient developed hyper infection and died two days after having started therapy with thiabendazole [149]. Unfortunately autopsy was denied.…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA) using filariform larval antigen may be employed for the diagnosis of strongyloidiasis [82 ]. Mayayo et al [83] described one patient with strongyloidiasis whose chest x-ray film showed pulmonary condensation that resembled a neoplastic lesion. In severe cases, chest radiography may reveal diffuse interstitial infiltrates, segmental or diffuse alveolar infiltrates, or pleural effusion [25 ,26,69,70].…”
Section: Strongyloidiasismentioning
confidence: 99%
“…Nodular pulmonary lesions caused by S. stercoralis have been rarely reported too, and in particular, there is no information on their frequency in asymptomatic patients. 10,11 They might derive from the migration of the larvae to the lungs, as suggested by Dogan and others, who found granulomas surrounding S. stercoralis larvae in the histological examination of lung biopsies performed in a patient. 10 We prescribed a chest X-ray for a general assessment of the patient, in absence of respiratory complaints.…”
Section: Discussionmentioning
confidence: 99%